ESSENTIAL OILS AND THEIR ANTIMICROBIAL EFFECTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This review explores the antimicrobial mechanisms, clinical applications, and therapeutic potential of essential oils, with a focus on pediatric and neonatal care. It highlights their ability to disrupt microbial membranes, inhibit metabolism, and suppress virulence factors. Evidence shows efficacy against multidrug-resistant pathogens, suggesting essential oils as valuable adjuvants amid rising antibiotic resistance. The review also addresses optimal formulations, delivery methods, and safety considerations, particularly for vulnerable populations. Future directions include nanotechnology-based delivery and standardized clinical protocols.